2022
DOI: 10.3389/fgene.2022.992073
|View full text |Cite
|
Sign up to set email alerts
|

Molecular prevalence of HBB-associated hemoglobinopathy among reproductive-age adults and the prenatal diagnosis in Jiangxi Province, southern central China

Abstract: Background and aims: Hemoglobinopathy associated with the HBB gene, with its two general subtypes as thalassemia and abnormal hemoglobin (Hb) variants, is one of the most prevalent hereditary Hb disorders worldwide. Herein we aimed to elucidate the prevalence of ß-thalassemia and abnormal hemoglobin variants and the prenatal diagnosis of the HBB gene in Jiangxi Province, southern central China.Methods: Hematological indices and capillary Hb electrophoresis were conducted for 136,149 subjects who were admitted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
(36 reference statements)
0
2
0
1
Order By: Relevance
“…Quanzhou region of Fujian province, located in Southeast China, displays a high prevalence of thalassemia, with a diversity and complexity of thalassemia 21 23 . Common α- and β-thalassemia gene variants in China are typically diagnosed by PCR-RDB and gap-PCR 12 , but they have limitations in the diagnosis of rare thalassemia variants. Third-generation sequencing technology has significant advantages in the diagnosis of thalassemia, and can detect almost all known globin gene variants 13 , 14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quanzhou region of Fujian province, located in Southeast China, displays a high prevalence of thalassemia, with a diversity and complexity of thalassemia 21 23 . Common α- and β-thalassemia gene variants in China are typically diagnosed by PCR-RDB and gap-PCR 12 , but they have limitations in the diagnosis of rare thalassemia variants. Third-generation sequencing technology has significant advantages in the diagnosis of thalassemia, and can detect almost all known globin gene variants 13 , 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Common α- and β-thalassemia gene variants in China are typically diagnosed by PCR-reverse dot blot hybridization (PCR-RDB) and gap-PCR 12 . However, traditional diagnostic tools may lead to misdiagnosis of rare thalassemia genotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Sebagai molekul protein yang berperan penting dalam pengangkutan oksigen, kekurangan atau bahkan tidak disintesisnya salah satu rantai globin berdampak pada kegagalan fungsi hemoglobin. Dalam 2 dekade terakhir telah banyak dilaporkan kasus kelainan genetik terkait hemoglobin di seluruh dunia termasuk Indonesia, diantaranya thalassemia dan hemoglobinopati (varian hemoglobin) (Luo et al, 2022;Modell & Darlison, 2008;Tangvarasittichai, 2011;Weatherall & Clegg, 2001;Wulandari, 2016).…”
Section: Pendahuluanunclassified
“…Our work may serve as a foundation for genetic counselling, public awareness campaigns, and as a guide to enhance ß-thal prevention. 20 ME Fields et al(2022) did a study to concluded that children with non-SCAs had higher OEF than unaffected children, indicating that anaemia is the main cause of this compensatory mechanism. However, even adjusting for the effect of anaemia, children with SCA have considerably higher OEF than kids without SCAs, indicating that there are other pathophysiologic mechanisms in SCA than anaemia that affect cerebral metabolic demand.…”
Section: Study Statusmentioning
confidence: 99%